PROFIL PEMAKAIAN GIGI TIRUAN LEPASAN BERBASIS AKRILIK PADA MASYARAKAT KELURAHAN BAHU KECAMATAN MALALAYANG - Khoman, Johanna A; Mariati, Ni Wayan; Siagian, Ellys D (JURNAL BIOMEDIK : JBM, 2012)
Abstract: A survey of denture wearing in Indonesia (2007) showed 4.5% used. This is caused by a low level of public knowledge about the actual function of dentures. The reasons that people do not wear dentures are: do not know about dentures, do not know the place of manufacturing, the expense of dentures, and the discomfort when wearing dentures. The purpose of this study was to find out the profile of using removable acrylic dentures (partial or full) among the people at Kelurahan Bahu Kecamatan Malalayang. This was a descriptive survey with a total sample of 154 respondents. The results showed that wearers of removable partial dentures were mostly females (39.6%), while wearers of full dentures were mostly males (13.7%). Removable partial denture wearers were mostly in the age group of 21-40 years (54.5%); and full denture wearers were mostly in the 60â€™s age group (16.9%). Aesthetics was the most frequent reason that respondents wore dentures (74%), compared to the restoration of the masticatory function (26%). Most wearers of removable dentures, either partial (41%) or full (9.7%), were high school educated. Conclusion: most denture wearers were high school educated and aesthetics was the most frequent reason. Wearers of removable partial dentures were mostly females while of full dentures were mostly males; and removable partial denture wearers were mostly in the younger ages comparing to the full denture ones. Keywords: denture wearer, removable denture, acrylic-basedÂ Abstrak: Survei pemakaian gigi tiruan di Indonesia (2007) menunjukkan tingkat pemakaian sebesar 4,5%. Hal ini antara lain disebabkan tingkat pengetahuan masyarakat tentang pemakaian gigi tiruan masih rendah sehingga masyarakat belum mengetahui fungsi gigi tiruan yang sebenarnya. Alasan tidak memakai gigi tiruan yakni tidak tahu tentang gigi tiruan, tidak mengetahui tempat pembuatan, harga yang mahal, dan kurang nyaman setelah menggunakan gigi tiruan. Tujuan penelitian ini untuk mengetahui gambaran pemakaian gigi tiruan lepasan berbasis akrilik pada masyarakat Kelurahan Bahu Kecamatan Malalayang, meliputi gigi tiruan sebagian lepasan (GTSL) dan gigi tiruan penuh (GTP). Jenis penelitian survei deskriptif dengan sampel total 154 responden. Hasil penelitian menunjukkan bahwa pengguna GTSL terbanyak pada responden perempuan (39,6%), sedangkan pengguna GTP terbanyak pada responden laki-laki (13,7%). Pengguna GTSL terbanyak pada kelompok usia 21-40 tahun (54,5%) dan pengguna GTP terbanyak pada kelompok usia > 60 tahun (16,9%). Estetik merupakan alasan utama memakai gigi tiruan (74%) dibandingkan mengembalikan fungsi pengunyahan (26%). Pengguna terbanyak gigi tiruan lepasan, baik GTSL (41%) maupun GTP (9,7%) memiliki tingkat pendidikan akhir SMA. Simpulan: pengguna gigi tiruan umumnya memiliki tingkat pendidikan akhir SMA dengan estetik sebagai alasan menggunakannya. GTSL terbanyak digunakan oleh responden perempuan sedangkan GTP terbanyak pada responden laki-laki; selain itu, kelompok usia GTSL lebih muda dibandingkan dengan GTP.Kata kunci : pemakai gigi tiruan, gigi tiruan lepasan berbasis akrilik